2015
DOI: 10.3846/mla.2015.811
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Heavy Metals Leaching From (Bio)char Obtained From Industrial Sewage Sludge / Iš Gamybinio Nuotekų Dumblo Pagamintos Bioanglies Sunkiųjų Metalų Išplovimo Įvertinimas

Abstract: Abstract. Biochar can be produced from many various feedstock including biomass residues such as straw, branches, sawdust and other agricultural and forestry waste. One of the alternatives is to obtain biochar from industrial sewage sludge, however, the use of such a product could be limited due to high quantities of heavy metals in the biochar as a product. Total concentration of heavy metals provides only limited information on the behavior of heavy metals, therefore, batch leaching and up-flow percolation l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…Peckyte and Baltrenaite studied the properties of carbonized products obtained from residues of various types of the sludges from paper and leather industries [32]. The performed research indicated that the form of biochar restrained the leaching of heavy metals [32], despite the concentrations being considerable when compared with the restrictions set by the regulations [33].…”
Section: Torrefaction Of Sewage Sludgementioning
confidence: 99%
See 1 more Smart Citation
“…Peckyte and Baltrenaite studied the properties of carbonized products obtained from residues of various types of the sludges from paper and leather industries [32]. The performed research indicated that the form of biochar restrained the leaching of heavy metals [32], despite the concentrations being considerable when compared with the restrictions set by the regulations [33].…”
Section: Torrefaction Of Sewage Sludgementioning
confidence: 99%
“…Peckyte and Baltrenaite studied the properties of carbonized products obtained from residues of various types of the sludges from paper and leather industries [32]. The performed research indicated that the form of biochar restrained the leaching of heavy metals [32], despite the concentrations being considerable when compared with the restrictions set by the regulations [33]. Wang et al performed an assessment of the environmental effects of the carbonization of sewage sludge and concluded that it may have an overall positive environmental impact in comparison with landfilling and incineration [34].…”
Section: Torrefaction Of Sewage Sludgementioning
confidence: 99%
“…An up-flow percolation test was performed in order to determine the leaching behaviour of BCs, as fully described in Peckyte and Baltrenaite (2015). Columns were packed with 137.5 g BCWC450, 130.8 g BCWC700, 210.5 g BCLG450, and 316.7 g BCLG700.…”
Section: Up-flow Percolation Testmentioning
confidence: 99%
“…Pyrolysis of sludge has been a subject of a significant amount of studies [36][37][38][39][40]. Baltrenaite and Peckyte studied the properties of pyrolysis product of various types of industrial sewage sludge (from paper and leather industries) [41]. Performed research indicated, that the form of biochar restrained leaching of heavy metals [41], despite that concentrations were considerable, when compared with the restrictions set by the regulations [42].…”
Section: Dry and Wet Torrefaction And Pyrolysis Of Sewage Sludgementioning
confidence: 99%
“…Baltrenaite and Peckyte studied the properties of pyrolysis product of various types of industrial sewage sludge (from paper and leather industries) [41]. Performed research indicated, that the form of biochar restrained leaching of heavy metals [41], despite that concentrations were considerable, when compared with the restrictions set by the regulations [42]. Assessment of environmental effects performed by Wang et al concluded that carbonization of the sewage sludge has overall positive environmental impact in comparison with landfilling and incineration [43].…”
Section: Dry and Wet Torrefaction And Pyrolysis Of Sewage Sludgementioning
confidence: 99%